Work Performance in Improving the Public Service Quality - Abbas, Muhammad Natsir; Rahmadanita, Annisa (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
The insufficient public knowledge in Semuntai Village, Long Ikis District, Paser Regency, regarding the completeness of service application files results in delays, compelling community members to make multiple visits. This qualitative descriptive study aimed to analyze employee performance in improving public services. Interviews with employees and community members, coupled with observations and document analysis, revealed commendable skills in technology, data processing, societal understanding, and public speaking, despite discrepancies in employee placement based on knowledge. Employee discipline, especially concerning office hours, needs improvement, yet personal efforts to enhance work quality through technical guidance and workshops are evident. Persistence in task execution is notable. In terms of work dimensions, cost-saving practices are in place, but punctuality issues persist, and while technology proficiency is noteworthy, deficiencies remain in supporting facilities and infrastructure. Overall, Semuntai Village employee performance is fairly good, with areas such as discipline, skills, time flexibility, and infrastructure support identified for improvement in public service delivery.